Estrategias para la gestión de la innovación: Pasado, Presente y Futuro (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
The innovation is developed as one of the primary factors in developing economies, where its study becomes the reason and essence of the programs and projects of institutions and countries. The present paper presents two philosophies in management development for TRIZ innovation and design thinking, disciplines that have been extensively addressed by researchers and scientists. The study is based on secondary sources of information; its structure contains elements described by different authors and presents conclusions and recommendations on the development of innovation management for Colombian companies.
Keywords: TRIZ; Innovation; desing thinking